Capacity and Strategy in Pension Reform: The Case of the “cédula viva” (Law N° 20530) in Peru - Alza Barco, Carlos; Dyer Cruzado, Henry (Universidad del Pacífico, 2016)
The pension system for public servants referred to as “20530” or the “cedula viva” caused severe fiscal damage to the Peruvian state until its reform in 2004. The reform was particularly difficult to accomplish because a number of senior officials and former government authorities were elite beneficiaries of this pension regime. In this article, we explore the reform process led by a government agency, identifying this agency’s capacity and the implementation of a strategy of visibilization as key factors.